Diabetes‐related foot disease in Australia: a systematic review of the prevalence and incidence of risk factors, disease and amputation in Australian populations - Yuqi Zhang; Jaap J. vanNetten; Mendel Baba; Qinglu Cheng; Rosana Pacella; Steven M. McPhail; Susanna Cramb; Peter A. Lazzarini (Journal of Foot and Ankle Research, 2021)
Abstract Background Diabetes‐related foot disease (DFD) is a leading cause of global hospitalisation, amputation and disability burdens; yet, the epidemiology of the DFD burden is unclear in Australia. We aimed to systematically review the literature reporting the prevalence and incidence of risk factors for DFD (e.g. neuropathy, peripheral artery disease), of DFD (ulcers and infection), and of diabetes‐related amputation (total, minor and major amputation) in Australian populations. Methods We systematically searched PubMed and EMBASE databases for peer‐reviewed articles published until December 31, 2019. We used search strings combining key terms for prevalence or incidence, DFD or amputation, and Australia. Search results were independently screened for eligibility by two investigators. Publications that reported prevalence or incidence of outcomes of interest in geographically defined Australian populations were eligible for inclusion. Included studies were independently assessed for methodological quality and key data were extracted by two investigators. Results Twenty publications met eligibility and were included. There was high heterogeneity for populations investigated and methods used to identify outcomes. We found within diabetes populations, the prevalence of risk factors ranged from 10.0–58.8%, of DFD from 1.2–1.5%, and the incidence of diabetes‐related amputation ranged from 5.2–7.2 per 1000 person‐years. Additionally, the incidence of DFD‐related hospitalisation ranged from 5.2–36.6 per 1000 person‐years within diabetes populations. Furthermore, within inpatients with diabetes, we found the prevalence of risk factors ranged from 35.3–43.3%, DFD from 7.0–15.1% and amputation during hospitalisation from 1.4–5.8%. Conclusions Our review suggests a similar risk factor prevalence, low but uncertain DFD prevalence, and high DFD‐related hospitalisation and amputation incidence in Australia compared to international populations. These findings may suggest that a low proportion of people with risk factors develop DFD, however, it is also possible that there is an underestimation of DFD prevalence in Australia in the few limited studies, given the high incidence of hospitalisation and amputation because of DFD. Either way, studies of nationally representative populations using valid outcome measures are needed to verify these DFD‐related findings and interpretations.